MeViSis simulator: an educational resource for teaching earthquake-resistant structures - Ponce Torres, Edison (2020)
This research work shows the development and implementation of MeViSis. The simulator was designed to support the teaching-learning process of the courses of the Faculty of Civil Engineering, for example, the resistance of materials, structures, seismology, among others. The tool is very important since the simulator allows the student to visually show the effects of an earthquake and the resistance of materials. The simulator was tested by ten students from the last semesters of Civil Engineering, and they are satisfied with the use of the tool.